Prevalence and factors associated with satisfaction of graduates of the Nursing course (Brazilian Journal of Health Research, 2021)
Objective: To analyze the prevalence and factors associated with the satisfaction of graduates of the undergraduate nursing course at a public university in the Brazilian Midwest. Method: Cross-sectional study, involving 221 graduates from 1979 to 2010. Data were collected using the Lime Survey software guided by a structured form. Results: The age of the graduates varied from 23 to 60 years with a median of 28 years, predominantly female, single, without children from private education. The prevalence of graduates working and satisfied with their education was 89.24%; the dissatisfied 70.46% due to the salary. The factors associated with satisfaction with nursing education showed that graduates who completed the course up to 23 years of age were more likely to be satisfied; those over the age of 30 who attended graduate school, worked in assistance, received up to nine minimum wages and had a public job were more satisfied with the salary of the profession. However, the most satisfied with nursing were the graduates who completed graduation in 2008, aged up to 30 years old, had postgraduate degrees, participated in scientific activities and worked more than 40 hours a week. Conclusion: The study may serve as an instrument for the temporal evaluation of the undergraduate nursing course and its institutionalization for systematic monitoring of graduates and support improvement actions to strengthen training, professional practice and enhance the satisfaction of graduates
Keywords: Education Nursing; Students Nursing; Staff Development; Job Market; Job Satisfaction